PENGEMBANGAN PROGRAM KEMITRAAN ANTARA PEMERINTAH KELURAHAN DAN LEMBAGA PEMBERDAYAAN MASYARAKAT DI KELURAHAN MAASING KECAMATAN TUMINTING KOTA MANADO - RACHMAN, ISMAIL (Sam Ratulangi University, 2017)
Community Empowerment Institution or LPM in Indonesian language is an organization formed bysociety initiatively as a partnership organization with the government to contain and deliver the society?sopinion especially about development.The position of LPM in the society is very important and strategic because this institution is the tool todeliver and contain the aspiration of the society and also an organization to encourage the society toparticipate in every aspect of development in the village. LPM basically is giving more space inimplementing the democracy especially for the society.LPM as the partner of the government can contain, facilitate and deliver the message or aspiration fromthe society. The other activity of LPM is facilitate every activity through the program that has beenproposed before by the society.Keyword: Program Development, Community Empowerment